Daily oral supplementation of Hochu-Ekki-To prevents osteoclastic activation and bone loss in ovariectomized mice - Shinsuke Ochiai; Kazuya Tokumura; Gyujin Park; Kakeru Ozaki; Tetsuhiro Horie; Takanori Yamada; Sayuki Iwahashi; Kaname Ohta; Hiroki Fusawa; Yasuka Okayama; Katsuyuki Kaneda; Takashi Iezaki; et al. (Elsevier, 2021)
Bone remodeling is sophisticatedly regulated by two different cell types: bone-resorbing osteoclasts and bone-forming osteoblasts. Hochu-Ekki-To, a Japanese traditional herbal medicine, is commonly used for the treatment of chronic diseases or frailty after an illness; however, its effects on metabolic bone diseases such as osteoporosis are not well known. We herein report that daily oral Hochu-Ekki-To administration significantly inhibits osteoclast activation as well as the reduction in bone volume in ovariectomized mice. Our results suggest that supplementation with Hochu-Ekki-To might be beneficial for the prophylaxis and treatment of metabolic bone diseases associated with abnormal osteoclast activation.